Beginning Ruby on Rails E-Commerce - Hellsten, Christian (Apress, 2012)
Beginning Ruby on Rails E-Commerce is for people who want to learn how to build realworld professional web applications using Rails best practices. We put a specific emphasis on e-commerce by showing you how to build an online bookstore, including a shopping cart, catalog, forum, and other functionality. On the front-end, we guide you through important technologies like Ajax, syndication, tagging, and internationalization. On the back-end, we show you how to integrate with payment gateways, use ActiveRecord and the Ferret search engine, and many other techniques. This book is also targeted at people who already have written an application or two using Rails, but who want to learn more about how test-driven development (TDD) can improve the quality of their code, and how to go beyond the standard test features built inside Rails. We will guide you through all the phases of a professional e-commerce project, from concept to production deployment and maintenance. In the first chapters, we show you how to jump-start your project and build a good, solid foundation for it, using agile practices like TDD. In later chapters, we dig deeper into Ruby on Rails, covering common requirements, such as translating your application into multiple languages and debugging production problems. Beginning Ruby on Rails E-Commerce is not intended to be a reference manual for Ruby on Rails. You can find many online resources and other books that provide a complete reference to the Ruby on Rails API and features, and these are mentioned throughout this book.